THE INFLUENCE OF PERSONAL FINANCIAL KNOWLEDGE AND PERSONAL FINANCIAL ATTITUDE TOWARDS BUYING DECISION USING CREDIT CARD IN MANADO CITY - Takaendengan, Luke Andre (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT Abstract: Many types of payment methods that can be used by consumers to meet all kinds of needs. Credit card is a phenomenon in the modern economic world. Present, credit card give consumers with so many advantages and conveniences offered. Some of the financial crisis that occurred in the community caused by the misuse of credit card facilities. With psychology approach, there are two factors that can used as the major determinants of credit card practices, there are: Personal Financial Knowledge and Personal Financial Attitude. The finding from this study states that Personal Financial Knowledge and Personal Financial Attitude has positive effects towards Buying Decision using Credit Card in Manado. Sample determined for 50 consumers. Tools of analysis using Multiple Regression, hypothesis test using F test and T test. Result of the findings is Y = -0.948 + 0.687X1 + 0.383X2 + e which shows that an increase in all independent variables (X) leads to a positive change of unit in buying decision using credit card as dependent variable both simultaneously and partially. Keywords: Financial Knowledge, Financial Attitude, Buying Decision, Credit Card.